Training organization and physiological profile of a 25-km open water world champion - Pla, R.; Aubry, A.; Merino, M.; Hellard, P. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Purpose: This case study describes the training of a world champion in open water swimming and some physiological variables over the 20 weeks before his title. Methods: Training volume and intensity were collected by a sport scientist using the coach`s daily reports and tests were performed to measure physiological adaptations. Results: The swimmer presents: VO2peak: 58.5 ml/ min/kg, maximal heart rate: 178 beats per minute, and maximal ventilation: 170 L/min. Weekly training volume was 85 ± 21 km with 12 ± 1 sessions, corresponding to 28 ± 4 hours per week. Training performed at intensities < 2 mmol/L (Z1) was 38.8 ± 7.5% of total training volume, 52.7 ± 7.9% between 2 mmol/L and 4 mmol/L (Z2) and 8.5 ± 4.2% > 4 mmol/L-1 (Z3). Conclusion: Training volume was higher than volume described in previous reports in elite swimmers. Training intensity showed a model marked by a large part conducted between 2 mmol/L and 4 mmol/L. Kinematics show a high swim index at this intensity and could explain why the swimmer dedicated a large part of training in Z2. Another finding highlights the speed corresponding to 4 mmol/L as a good endurance indicator.